Nothing if not tenacious. (Economist, 2001)
Reports on the business practices of software company Microsoft. Their plans to ship their product Windows XP; Appeal of the company to the United States Supreme Court to have the antitrust case against them thrown out; View that Windows XP repeats Microsoft's original misconduct; Details on Microsoft's anticompetitive behavior.